PENGARUH MODEL KOOPERATIF TIPE MAKE A MATCH BERBANTUAN MEDIA BUKU DIGITAL LITERACY CLOUD TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN TEKS NARASI SISWA - Ninda Washilatul Hasanah; Indah Nurmahanani; Primanita Sholihah Rosmana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The aim of this research is of course to find out how much influence the make a match type cooperative model assisted by digital literacy cloud book media has on students' ability to read and understand narrative texts. Researchers used a quasi-experimental type of research with a nonequivalent control group design. The subjects in this research were 22 class IVA students and 22 class IVB students. The instrument used in this research was a test of the ability to read and understand narrative text. The results obtained from the influence of the make a match type cooperative model assisted by digital literacy cloud book media on students' ability to read and understand narrative text were 34.1%. So it can be concluded that students who received the make a match type cooperative learning model assisted by digital literacy cloud book media were better than students who received the think pair and share type cooperative learning model